2015
DOI: 10.1111/ajpy.12078
|View full text |Cite
|
Sign up to set email alerts
|

Examining the predictive value of combining the theory of planned behaviour and the volunteer functions inventory

Abstract: Objective:The research investigated whether a stronger predictive model of volunteering behaviour prevails when the functions of the volunteer functions inventory are combined with the constructs of the theory of planned behaviour. The study advances on prior research which either examined the predictive capacity of each model or compared their explanatory values. Method: The survey was completed by 186 individuals (Male = 56.10%; Mean Age = 63.7 years) who were retired or approaching retirement and within the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 30 publications
3
23
0
Order By: Relevance
“…Further, Garver et al ( 2009 ) found that students volunteer for certain organizations when they know current volunteers or that organization, Dunn et al ( 2016 ) found that socializing was noted as among the common motives for volunteerism. Brayley et al ( 2015 ) found that subjective norms were the strongest predictor of willingness to volunteer. All of these findings seem to corroborate the impact that social influence can have on individuals’ volunteerism behavior.…”
Section: Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, Garver et al ( 2009 ) found that students volunteer for certain organizations when they know current volunteers or that organization, Dunn et al ( 2016 ) found that socializing was noted as among the common motives for volunteerism. Brayley et al ( 2015 ) found that subjective norms were the strongest predictor of willingness to volunteer. All of these findings seem to corroborate the impact that social influence can have on individuals’ volunteerism behavior.…”
Section: Hypothesesmentioning
confidence: 99%
“…Of the many contexts that have served as a backdrop for the study of volunteerism are Ajzen’s ( 1988 ) Theory of Planned Behavior in which behavior is preceded by intentions, which is influenced by attitudes, subjective norms, and perceived behavioral control. For instance, Brayley et al ( 2015 ) found that motives for volunteering were, in order of strength, subjective norms, attitude, understanding, and perceived behavioral control. Another is the functional approach to volunteering which posits that individuals will volunteer if one or more of six motivational functions (altruistic value expression, understanding, career, social, protective and esteem) are perceived to be fulfilled (Clary et al 1992 ).…”
Section: Introductionmentioning
confidence: 99%
“…The theory of planned behaviour (TPB; Ajzen, 1985Ajzen, , 2011 states that subjective norms (i.e. the perceived social approval of engaging or not engaging in a behaviour) are essential in the process of deciding to volunteer (Brayley et al, 2015). In the mentoring context, this means that when mentors feel the support of significant others, they are more likely to stay engaged in the programme and continue mentoring.…”
Section: Factors Contributing To Volunteer Role Identitymentioning
confidence: 99%
“…Individual characteristics, such as age, social background, resources, and health status, help predict an individual's voluntary action participation [48][49][50]. Motives such as altruism, self-actualization, need for power, need for mutual support, and self-esteem explain many aspects of volunteer behavior [51][52][53][54][55][56][57]. Organizational factors affecting volunteers such as an organization's values and attitudes have also been studied [58].…”
Section: Motivation and Willingness To Volunteermentioning
confidence: 99%